Evaluation Of Anti-Hyperlipidemic Potentials Of Aqueous Fruit Pulp Extract Of Adensonia Digitata In Experimental Rats - A.J., Alhassan; I.U., Muhammad; I.K., Jarumi; A.M., Wudil (European Scientific Journal, ESJ, 2016)
Introduction: Hyperlipidemia is a modifiable risk factor of an important killer disease “cardiovascular diseases”, research work exploring anti- hyperlipidemic activity of local plant is timely gesture. Aim: To investigate anti-hyperlipidemic ability of aqueous fruit pulp extract of Adensonia digitata in experimental rats. Methodology: Hyperlipidemia was induced in rats via feeding on high lipid diet (HLD) for 3 weeks. A total of 42 rats used, were divided into seven groups (GI - GVII) of six rats each. GI served as normal control, GII were normal rats administered with only the extract and GIII serves as hyperlipidemic control group. While GIV, GV and GVI were hyperlipidemic group administered with the extract at a dose of 1.25g/kg, 2.5g/kg and 3.75g/kg body weight respectively and GVII were hyperlipidemic given standard hyperlipidemic drug (atorvastatin), the hyperlipidemic rats were on high cholesterol diet throughout the study period. At the end of the first week of extract administration, three animals from each group were randomly selected and sacrificed. At the end of the second week, the remaining three animals from each group were also sacrificed and serum was collected for analysis of serum lipid profile (Total Cholesterol, LDL-Cholesterol, HDL-Cholesterol and Triglyceride). Results: Significant decrease (p< 0.05) in the serum TC, TG, LDL-C, and a significant increase in the HDL-C levels was observed with 1.25g/kg, 2.50g/kg and 3.75g/kg in group IV, V and VI, and group VII treated with Atorvastatin when to compared with the hyperlipidemic control both in the first and second week of treatment. Conclusion: The study demonstrated that A. digitata aqueous fruit pulp extract possesses anti-hyperlipidemic property. The effects may be associated with the phytochemical content of the plant pulp. Further studies on the plant may focus on identification, isolation of active component(s) aimed at formulating anti-hyperlipidemic drugs from natural source.